The effectiveness of spatholobus littoralis hassk ethanol extract against fungal growth of candida albicans - Verent Novianti Liunardy; Enny Marwati Suwandi (Jurnal Kedokteran Gigi Terpadu, 2023)
Candida albicans is a normal oral flora which has a virulence factor that is closely associated with Oral Candidiasis. Both bacteria have a symbiotic relationship in growth and production of biofilms. Spatholobus littoralis Hassk stem are often not known for their benefits so they are not utilized optimally and effectively. Spatholobus littoralis Hassk stem contains active ingredients in the form of tannins, alkaloids, triterpenoids, saponins, and flavonoids which are antifungal. Objectives: To determine the antifungal effects of ethanol extract bajakah tampala stem (Spatholobus littoralis Hassk) on C. albicans. Methods: In vitro laboratory experiment with post test only control group design. The test solutions used were ethanol extract of bajakah tampala stem (Spatholobus littoralis Hassk) 6.25%, 12.5%, 25%, 50% and 100%, nystatine as a positive control, and aquades 10% as a negative control. The antifungal test was carried out using the plate count method. Results: All concentrations of the extracts has a antifungal effect on C. albicans compared to the negative control (p<0,05). Conclusion: The ethanol extract of Spatholobus littoralis Hassk stem is effective in inhibiting the growth of the Candida albicans. Further studies on toxicity of Spatholobus littoralis Hassk stem ethanol extract on Candida albicans are necessary.